2004
DOI: 10.1345/aph.1d524
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Recurrent Perforating Intestinal Ulcers with Thalidomide in Behçet's Disease

Abstract: Thalidomide may be an effective alternative treatment for BD patients with recurrent and perforating intestinal ulcers despite intense immunosuppressive therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…1 Substantial evidences show a pivotal role for proinflammatory Cytokines (e.g., interleukin1, interleukin6, and tumor necrosis factor-␣) in induction of CNS mediated responses such as fever, somnolence, and sickness behavior in acute infections. 4 We suggest that these drugs, which are approved by FDA for some of the aforementioned diseases, can be useful in treating patients with chronic fatigue syndrome. 2 Recently, biological agents that bind and neutralize the tumor necrosis factor have become available: 1) Etanercept, a tumor necrosis factor type 2 receptor fused to IgG1, is assessed to be effective in psoriasis.…”
Section: Potential Drugs For Improving Chronic Fatigue Syndromementioning
confidence: 99%
“…1 Substantial evidences show a pivotal role for proinflammatory Cytokines (e.g., interleukin1, interleukin6, and tumor necrosis factor-␣) in induction of CNS mediated responses such as fever, somnolence, and sickness behavior in acute infections. 4 We suggest that these drugs, which are approved by FDA for some of the aforementioned diseases, can be useful in treating patients with chronic fatigue syndrome. 2 Recently, biological agents that bind and neutralize the tumor necrosis factor have become available: 1) Etanercept, a tumor necrosis factor type 2 receptor fused to IgG1, is assessed to be effective in psoriasis.…”
Section: Potential Drugs For Improving Chronic Fatigue Syndromementioning
confidence: 99%
“…Although clinical evidence is lacking, thalidomide and its analog lenalidomide are sometimes used for the management of CD,262728 and there are several studies that report the efficacy of thalidomide in intestinal BD 2930313233. Travis et al29 reported that thalidomide was used for maintenance therapy in patients treated with IFX.…”
Section: Medical Treatmentmentioning
confidence: 99%
“…In a report by Kari et al,31 5 pediatric BD patients were treated with thalidomide at 1 mg/kg/wk to 1 mg/kg/day, resulting in complete remission in 3 patients and clinical response in 2. Sayarlioglu et al32 reported a patient who required multiple surgeries due to intestinal perforations and was refractory to intense immunosuppressive therapies, including methylprednisolone and cyclophosphamide. Thalidomide (100 mg/day) was started after the third surgery, and the patient experienced no additional intestinal perforations during the follow-up period of 4 months.…”
Section: Medical Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of the drug was associated with an increase in erythema nodosum in the first 8 weeks of the study. Four patients developed polyneuropathy as complication of the treatment [72]. In another prospective study, 23 patients with BD and severe refractory oral or genital ulceration were treated with thalidomide.…”
Section: Thalidomidementioning
confidence: 99%